Alternative Method of Audio Searching (AMAS) (International Journal of Engineering and Computer Science, 2016)
With the advent of searching technologies becoming more and more efficient day by day it has become impertinent to apply the same on audio. Often times we require search results which if in audio format makes more sense. Our existing algorithms use waveforms to search on audio which requires indexing of all audio files or the audio file is matched via the names of the file itself and pertaining metadata about the file. In order to make real and real-time searching on the audio files possible we use this methodology. This paper merely outlines a possible way of searching for the content of the audio files. We do this by converting the audio to text  and then search on the text itself thus giving better results. In this paper we review on the previous works and provide a rough guideline how this can be achieved.